The Implementation of Tut Wuri Handayani Values at the Taman Muda Elementary School Jetis Yogyakarta - Sugiyanto, Sugiyanto; LN, Syamsu Yusuf; Supriatna, Mamat (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
This research aims to examine the noble values contained in tut wuri handayani and its implementation in education, which holds meaning as an educator or pamong who plays a role in developing students' abilities through the influence of education by providing freedom in learning to find the meaning of life. The research approach used in this study was phenomenology. The research method employed was hermeneutic phenomenology, which focuses on life experiences and interpreting the